Do Two Nonword Types Bring About Different YN Vocabulary Test Results? - Wongsirichan, Wallapha; Wannaruk, Anchalee; Ward, Jeremy (LEARN Journal: Language Education and Acquisition Research Network, 2022)
The YN vocabulary test (YN test) is a vocabulary size test that presents test takers with a list of words and asks them to answer yes to the words they know. This test may include nonwords, i.e., imaginary words added to the test to check for guessing. However, there have been no conclusive guidelines about nonword construction. One way of creating a nonword is to change one or two letters from the original word such as dactor from doctor. This approach suggests one important question: To what extent should nonwords be different from their original words? This study, therefore, aims to compare 2 nonword types: one type which is phonologically similar to real words (N1) and the other which is less similar (N2) in order to check whether they lead to different YN test results. An example of N1 would be willage, which is how some Thai speakers pronounce village while N2 would be cillage. Two YN test types (N1 and N2 tests) were administered to 600 university students, followed by translation tests and semi-structured interviews. The results suggest that N1 tests tend to be better in predicting the actual vocabulary size of the participants than N2.